2014
DOI: 10.3390/s140304712
|View full text |Cite
|
Sign up to set email alerts
|

Knitted Strain Sensors: Impact of Design Parameters on Sensing Properties

Abstract: This paper presents a study of the sensing properties exhibited by textile-based knitted strain sensors. Knitted sensors were manufactured using flat-bed knitting technology, and electro-mechanical tests were subsequently performed on the specimens using a tensile testing machine to apply strain whilst the sensor was incorporated into a Wheatstone bridge arrangement to allow electrical monitoring. The sensing fabrics were manufactured from silver-plated nylon and elastomeric yarns. The component yarns offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 34 publications
0
120
0
2
Order By: Relevance
“…On the other hand, our intention is to replace all cables, even the transmission lines carrying the RF signal, with conductive yarn routes on the firefighter suit [8][9][10][11]. Moreover, we intend to replace ECG sensors with textile electrodes, either based on conductive yarns or screen-printed [12,13], while respiration rate, temperature and skin moisture (perspiration) could be monitored using appropriately designed variations of conductive yarn based knitted sensors [14][15][16][17]. Finally, even the antenna could be partially or fully textile [18,19].…”
Section: Wearable Sensor Nodementioning
confidence: 99%
“…On the other hand, our intention is to replace all cables, even the transmission lines carrying the RF signal, with conductive yarn routes on the firefighter suit [8][9][10][11]. Moreover, we intend to replace ECG sensors with textile electrodes, either based on conductive yarns or screen-printed [12,13], while respiration rate, temperature and skin moisture (perspiration) could be monitored using appropriately designed variations of conductive yarn based knitted sensors [14][15][16][17]. Finally, even the antenna could be partially or fully textile [18,19].…”
Section: Wearable Sensor Nodementioning
confidence: 99%
“…Related research [7][8][9][10] studied the contacts between electro-conductive yarns embedded in knitted fabrics. Unlike in woven hybrid fabrics, in knitted fabrics, contacts appear between two consecutive conductive loops and not only at the intersection of weft and warp yarns.…”
Section: Methodsmentioning
confidence: 99%
“…Atalay et al [7] concluded that it is possible to manipulate the sensing properties of knitted sensors and the sensor response may be engineered by varying the production parameters applied to specific designs [8]. Zhang et al [9] created knitted strain sensors by using stainless steel and carbon yarns and identified that the contacting electrical resistance between overlapped fibers is the primary factor in the sensing mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This significantly broadens the potential for 'smart' product applications across industries associated to sports performance, ergonomics, rehabilitation, etc. where design customisation to individual user requirements of performance and quantitative evaluation is currently highly desirable [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%